2020
DOI: 10.1002/ael2.20033
|View full text |Cite
|
Sign up to set email alerts
|

A justification for continued management of turfgrass during economic contraction

Abstract: A novel coronavirus, termed COVID-19, spread worldwide and become a global pandemic in 2020. Forecasts show that COVID-19 will cause substantial economic contraction affecting almost every industry. Managed turfgrass, particularly in urban settings, has many positive societal and environmental benefits. In a contracted economy, will resources be available to manage turfgrass to achieve these benefits? In this paper, we outline the benefits of managed turfgrass on golf courses, playing fields, recreational park… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…The pandemic furthermore demonstrates the important role of urban green spaces, for example, and their potential to trigger the resilience people need to bounce back to its threats and to contribute to a higher quality of life. Venter et al (2020) have shown for Oslo that the recreational use of green space in residential areas, city parks and peri-urban areas has increased. Kleinschroth and Kowarik (2020) argue that further development of urban green infrastructure should be an integral part of key changes in response to the experience of the current crisis.…”
Section: Resilience As a Key Dimension Of Urban Sustainability Transformations And The Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…The pandemic furthermore demonstrates the important role of urban green spaces, for example, and their potential to trigger the resilience people need to bounce back to its threats and to contribute to a higher quality of life. Venter et al (2020) have shown for Oslo that the recreational use of green space in residential areas, city parks and peri-urban areas has increased. Kleinschroth and Kowarik (2020) argue that further development of urban green infrastructure should be an integral part of key changes in response to the experience of the current crisis.…”
Section: Resilience As a Key Dimension Of Urban Sustainability Transformations And The Covid-19 Pandemicmentioning
confidence: 99%
“…While several articles have been published on how Covid-19 possibly affects the way in which cities are organized (Megahed & Ghoneim, 2020;Sharifi & Khavarian-Garmsir, 2020;Venter, Barton, Gundersen, Figari, & Nowell, 2020) and why cities are a catalyst for the rapid spread of diseases such as Covid-19 (Neiderud, 2015), the impact of Covid-19 on the urban implementation of SDGs remains fuzzy. This is reflected, for example, in the UNESCO argumentation that the severe impact of the Covid-19 pandemic on cities raises fundamental questions about sustainable urban development, and indicates the need to rethink development strategies towards more resource efficiency, quality of life and resilience (UNESCO, 2020).…”
mentioning
confidence: 99%
“…Established sustainability goals set forth by the United Nations and the United States center upon mitigating increases in global temperature and protecting biodiversity to conserve ecosystem services 1 , 2 . Turfgrasses are perennial components of urban greenspaces found in parks, recreational areas, golf courses, sports fields, and lawns that confer a multitude of environmental and societal benefits from atmospheric enhancement to improved mental and physical well-being that have been reviewed in the literature 3 . Poa annua (annual bluegrass) is the most troublesome weed of managed turfgrass in urban greenspaces 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Many owners of turfgrass operations do not fully understand the agronomics of turfgrass management and therefore are unable to effectively evaluate the economic efficiency of the resources used. In our previous letter (Brosnan et al, 2020), we argued for the essentiality of turfgrass management to maintain a set of important societal and ecological benefits during a public health crisis. Here, we estimate economic minimums required for mowing, fertilizing, and irrigating turfgrasses across the United States to ensure those benefits.…”
Section: Introductionmentioning
confidence: 99%